An Evaluation of the Ottoman-Period Pipes in Bitlis Castle (2018 Excavation Seasion) - Sen, Korkmaz; Karasu, Yunus Emre (Istanbul Univ, Research Inst Turkology, Dept Art History, 2020)
This study's aim was to examine pipes, found in excavation works in 2018 in Bitlis Castle, which is located on a rocky region in the city centre of the Bitlis province. Pipe finds with a large number of different forms and decoration features were obtained in areas, called P and R 14-15 and a drilling in the excavation works in Bitlis Castle in 2018. As a base, out of these pipe finds sieve bowl pipes were examined in an earlier published study so they are excluded from the present one. Pipes, which were used to smoke along with coffee in coffeehouses, generally the socialization spaces in the Ottoman Empire, were also widely used in Bitlis, where tobacco was known to have been produced. The variety and abundance of pipe finds found during excavation works in Bitlis Castle indicate that pipes were used in the region to a high degree. Moreover, it is understood that different plants were used to smoke except for pipes, having distinct period characteristics in terms of form, size, additive, and decoration features. It is considered that pipe forms and types vary by local tastes and functional purpose. When pipe finds, composing the subject matter of the present study, are compared to other data collected in excavation works, and their similar samples, they may be dated to a period between the 17th and 19th centuries.
Bitlis Kalesi Osmanli Dönemi Lülelerinin De?erlendirilmesi (2018 Yili Kazi Sezonu)
Keywords: Bitlis Castle; the Ottoman State; Pipe; Excavation; Tobacco